Management of post-traumatic stress disorder symptoms by yoga: an overview - Nina Laplaud; Anaïck Perrochon; Matthieu Gallou-Guyot; Maarten Moens; Lisa Goudman; Romain David; Philippe Rigoard; Maxime Billot (BMC, 2023)
Abstract Background Posttraumatic stress disorder (PTSD) can occur after trauma. While PTSD management strategies include first-line pharmacotherapy and psychotherapy, mind-body therapies, such as yoga, are applied in the PTSD population. This overview aimed to summarize the effectiveness of yoga interventions on PTSD symptoms in adults in a systematic review (SR) including randomized controlled trials (RCTs). Method We searched for SR with or without meta-analysis of RCTs involving adults with PTSD diagnosis or trauma history. The search was conducted until April 2022, through six databases (Cochrane Database, MEDLINE (Pubmed), Scopus, Embase, CINHAL and PEDro). The primary outcome was the evolution of PTSD symptoms throughout the intervention. Secondary outcomes included follow-up, safety, adherence, and cost of the intervention. Two authors independently performed the selection, data extraction and risk of bias assessment with the AMSTAR 2 tool and overlap calculation. This overview is a qualitative summary of the results obtained in the selected studies. Results Eleven SRs were analyzed, of which 8 included meta-analyses. The overlap between studies was considered very high (corrected covered area of 21%). Fifty-nine RCTs involving 4434 participants were included. Yoga had a significant small-to-moderate effect-size on PTSD symptom decrease in 7 SRs and non-significant effects in 1 SR with meta-analysis. All SR without meta-analysis found beneficial effects of yoga on PTSD. Secondary outcomes were not sufficiently assessed to provide clear evidence. Results should be interpreted with caution as 1 SR was rated as at moderate risk of bias, 3 as low and 7 as critically low. Conclusions While yoga therapy seems promising for decreasing PTSD symptoms, future research should standardize yoga therapy duration/frequency/type and consider long-term efficacy to better delineate yoga therapy efficacy in PTSD patients.